Dinamika Temporal Dampak Pengelolaan Limbah Padat Terhadap Konsentrasi COD dan Amonia di Air Permukaan - Alloysius Pamurda Dhika M; Fadilla Ayu Fauzia; Mochamad Adhiraga Pratama (Jurnal Serambi Engineering, 2023)
AbstractRivers in Indonesia are heavily polluted by unmanaged municipal solid waste (MSW) which affects their capacity as drinking water, power, and irrigation sources. This research aimed to analyze the effect of MSW types and contact time on the dynamics of Chemical Oxygen Demand (COD) and ammonia in the waterthat was traced over two weeks period in a batch reactor filled with Ciliwung River organic and inorganic MSW samples. Then, the MSW degradation rates to COD and ammonia (k1) were mathematically analyzed by using the mass balance principle. The results showed that for organic MSW, there were rapid increasesin COD and ammonia concentrations on the first 6 days of the experiment and followed by steady decreases. In contrast, for inorganic MSW, overall steady trends were observed for both COD and Ammonia. The analysis of the degradation rate showed that the values of K1 for COD in organic MSW was ranging from3.841 to 4.655 /day, 10-30 times higher than those of inorganic MSW values, which ranged from 0.122 to 0.425 /day. For ammonia, the values of k1 for organic MSW ranged from 0.0021 to 0.0028 /day, about two times higher than those of inorganic MSW values ranging from 0.001-0.0014 /day. Findings in this studyoffer opportunities to model and simulate COD and Ammonia dynamics in surface water due to MSW contamination.Keywords: COD, ammonia, degradation, solid waste, time effect